Using Registers to Study Effectiveness and Safety of Drugs - L. Yu. Drozdova; N. P. Kutishenko; M. L. Ginzburg (Klinicist)
The article discusses the main aspects of registers use to evaluate the effectiveness and safety of drugs. It is noted that the results of the randomized clinical trials are currently constitute the highest level of evidence in medicine, but they have several limitations. Besides, in manycases evidence based on the results of the randomized clinical trials (RCTs) is simply missing. In this connection need for observational studies that, despite some limitations often supplement the information obtained in the RCT is discussed. Registers as the way to study the effectiveness and safety of drugs could help overcome some limitations of observational studies. The examples of both Russian and foreign studies held within registers in order to study the effectiveness of drugs in cardiology are provided. The framework for RCTs and registries contribution in studying effectiveness and safety of a drug is proposed.